David Griffiths and the missionary "History of Madagascar" - Campbell, Gwyn, 1952- (Studies in Christian Mission, 2012)
In 1838, William Ellis of the LMS published a History of Madagascar-considered a key primary source for nineteenth-century Malagasy history. Four years later, David Griffiths, longest serving member of the Madagascar Mission, published Hanes Madagascar ("History of Madagascar") in Welsh. Campbell's study explores the intriguing relationship between these works and their authors. It analyses the role of Griffiths; presents evidence that much of Ellis' History derived from Griffiths' research; and presents the first ever translation of Hanes Madagascar (with extensive annotations). This study suggests that the tensions arising from the different cultural perceptions of Welsh and English missionaries moulded the destiny of the Madagascar mission. It will hopefully inspire re-evaluation of other missions and their relationship to British imperial policy.